2021
DOI: 10.1002/aenm.202100190
|View full text |Cite
|
Sign up to set email alerts
|

Doping‐Induced Viscoelasticity in PbTe Thermoelectric Inks for 3D Printing of Power‐Generating Tubes

Abstract: Thermoelectric (TE) technologies offer promising means to enhance fossil energy efficiencies by generating electricity from waste heat from industrial or automobile exhaust gases. For these applications, thermoelectric modules should be designed from the perspective of system integration for efficient heat transfer, system simplification, and low processing cost. However, typical thermoelectric modules manufactured by traditional processes do not fulfil such requirements, especially for exhaust pipes. Hence, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…23 Moreover, the colloidal stabilities can also be assessed using stress sweep curves. 20 In the linear viscoelastic region, the storage modulus is approximately constant. When the shear stress is beyond the critical value, there is a sudden decrease in the modulus which indicates the deformation of colloidal structures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Moreover, the colloidal stabilities can also be assessed using stress sweep curves. 20 In the linear viscoelastic region, the storage modulus is approximately constant. When the shear stress is beyond the critical value, there is a sudden decrease in the modulus which indicates the deformation of colloidal structures.…”
Section: Resultsmentioning
confidence: 99%
“…Direct ink writing (DIW), a type of extrusion 3D printing technology, has recently emerged as a convenient and low-cost method of constructing custom-built shapes. [14][15][16] To date, many TE materials and devices including conducting polymers, 17,18 Bi 2 Te 3 -based, 13,19 PbTe-based, 20 and Cu 2 Se-based 21 compounds can be printed. Nevertheless, the ZT values of 3D-printed materials are lower than those of bulk counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee and colleagues found that undoped PbTe has an almost neutral surface charge as shown in Figure 6a. 116 Through the introduction of doping-induced surface charges on the TE particles, they managed to obtain viscoelastic inks suitable for DIW. Sodium dopants produce negatively charged PbTe particles, while doping with antimony produces positively charged PbTe particles.…”
Section: Modification Of Viscoelastic Properties Through Additivesmentioning
confidence: 99%
“…This is in stark contrast to the direct ink writing (DIW) techniques, which is an extrusion-based 3D printing method to create meso- and micro-scales architectures. By developing the viscoelastic inks containing inorganic particles, the DIW has been extensively utilized for fabricating various types of functional inorganic materials 18 20 . For example, the DLP-printed thermoelectric BiSbTe materials was reported to exhibit the ZT value of 0.12, which is one order of magnitude lower than that of inorganic bulk reference materials or that of even DIW-printed BiSbTe because the printed objects contain organic residues 21 .…”
Section: Introductionmentioning
confidence: 99%